Pengaruh Beban Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Penanganan Prasarana dan Sarana Umum di Kelurahan Cempaka Putih - Dwi Astuti Handayani; Saifullah (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The management of public infrastructure and facilities (PPSU) in Cempaka Putih Timur Urban Village plays a crucial role in maintaining cleanliness, order, and the upkeep of public facilities. However, various challenges affecting PPSU officers’ performance persist, including high workload, low work motivation, and an unsupportive work environment. This research aims to analyze and evaluate the influence of workload, work motivation, and work environment on the performance of PPSU officers in Cempaka Putih Timur Urban Village. This research employs a quantitative approach through a survey involving all 75 PPSU members in Cempaka Putih Timur Urban Village. Data were analyzed using multiple linear regression with SPSS software. The findings indicate that workload, work motivation, and work environment each have a positive and significant influence on performance. Simultaneously, these three independent variables contribute positively and significantly to PPSU performance, as reflected in the calculated F-value of 61.135, which exceeds the F-table value of 2.734, with a significance level of 0.000, lower than the α probability of 0.05. Additionally, the coefficient of determination (R²) is 0.709, indicating that workload, work motivation, and work environment collectively explain 70.9% of the variance in performance, while the remaining 29.1% is influenced by other factors. This research suggests the need for better workload management, enhanced work motivation programs, and an optimized work environment to improve PPSU performance.